Traditional Dayah Education in Aceh in the Perspective of Perennialist Philosophy - T. Wildan (At-Tafkir, 2022)
This study aims to analyze the existence of education in dayah in terms of perennialist philosophy. The problem that will be studied is the existence of the dayah education system and its relationship with the concept of perennialist philosophy. The research methodology is library research with a descriptive analysis approach. The findings of this study are: First: the curriculum in Aceh's dayahs has led to the refinement of a more modernist curriculum; many Islamic boarding schools in Aceh have integrated the general curriculum into the Islamic boarding school (dayah) curriculum so that there is a balance between public and religious education, even though religious education dominates the implementation curriculum. Second: learning methods, dayahs, have modernized learning methods, such as attending skills and art classes, entrepreneurial learning, financial management, etc. Third, dayahs have prepared students to face the world of industrialization and the needs of the world of work. Fourth, traditional dayahs still preserve the old culture and continue to present new things that are modernist to answer the challenges of the globalization era.